TVMS calculation and dynamic analysis of carburized spur gear pair. (1st March 2022) - Kumar, Vikash; Kumar, Anurag; Kumar, Sanjeev; Sarangi, Somnath
Highlights: The Time Varying Mess Stiffness (TVMS) of a carburized spur gear pair is derived analytically. Effect of carburization on TVMS of spur gear pair is studied. Severity of cracks at tooth root is examined and compared for both uncarburized and carburized spur gear pair. Behavior of characteristic frequencies and its sidebands at different crack depths are studied through cepstrum analysis. Uncarburized and carburized gear pair are successfully depicted by Spectral entropy analysis. Abstract: Carburized gear tooth are widely used in industries due to their more resistance to wear and abrasion. The top surface of the gear becomes hard due to carburization and offers more resistance to fault penetration developed on the surface of the gear. In gear modeling, the time-varying mesh stiffness (TVMS) is the characteristic feature that indicates the health of the gears in the system. Much research has been carried out on the calculation of TVMS of uncarburized gear and their gear dynamics have been studied for different faults condition on the system. This paper presents first time the mathematical formulation of carburized spur gear pair including the cracked tooth at the root of the pinion for the calculation of TVMS through the potential energy approach. TVMS of carburized and uncarburized spur gear pair are studied and compared analytically. The TVMS results show that the carburized gear pair has more stiffness than the uncarburized gear pair at different crack depths. Furthermore, the gear modeling of a single-stage carburized spur gear pair is also developed to study the effect of carburization on the dynamic behavior of the system at different crack depths. The vibration responses for both carburized and uncarburized gear pairs are obtained and compared at different crack depths. The cepstrum analysis is also carried out on vibration responses to analyze the impact of tooth cracks on the characteristic frequencies and their sidebands for both cases. At the end of this work, both carburized and uncarburized responses are compared through spectral entropy. The obtained results provide important guidelines regarding the condition monitoring and fault diagnosis of carburized spur gear pair at different tooth crack depths.